Estimating Weight of Patients With Acute Stroke When Dosing for Thrombolysis. Issue 1 (January 2016) - Barrow, Tom; Khan, Muhammad S.; Halse, Omid; Bentley, Paul; Sharma, Pankaj
Abstract : Background and Purpose—: Estimating patient weight forms an important part of emergency ischemic stroke management guiding the dose of alteplase (tissue-type plasminogen activator). Weighing patients with stroke can be logistically challenging and time consuming, potentially delaying treatment times. We aimed to assess the reliability of approximating weight to determine recombinant tissue-type plasminogen activator dose and whether potential inaccurate dosing affected patient outcomes. Methods—: Two hundred forty-two consecutive patients were studied at a large tertiary stroke center. Estimated and actual measured weight, alteplase dose, and pre-and post-modified Rankin Scale/National Institute of Health Stroke Scale outcome were recorded for each patient. Results—: Clinicians significantly underestimated weights by 1.13 kg (range, −43 to +18 kg; SD, 7.14; P <0.05). The difference between estimated and actual weight proved to be greatest in the heaviest third of patients (−4.51 kg; SD, 8.35; P <0.001), resulting in 19.7% of patients receiving a deviation of at least 10% from the recommended recombinant tissue-type plasminogen activator dose. On average, the heaviest third of patients received an underdose of 0.04 mg/kg and were found to have a greater baseline National Institute of Health Stroke Scale on admission ( P <0.001). National Institute of Health Stroke Scale improvement by day 7 or on discharge was significantly reduced in patients weighing >78 kg (National Institute of Health Stroke Scale score difference of 4.0 points, P <0.05) than in lighter individuals. Conclusions—: Clinicians are poor at approximating the weights of patients with stroke in the acute setting, especially when patients lie at the extremes of weight. Beds capable of weighing patients should be mandated in emergency rooms for patients with acute stroke. Abstract : Supplemental Digital Content is available in the text.